2021
DOI: 10.1007/s11432-020-3071-8
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory prediction of cyclist based on dynamic Bayesian network and long short-term memory model at unsignalized intersections

Abstract: Cyclist trajectory prediction is of great significance for both active collision avoidance and path planning of intelligent vehicles. This paper presents a trajectory prediction method for the motion intention of cyclists in real traffic scenarios. This method is based on dynamic Bayesian network (DBN) and long short-term memory (LSTM). The motion intention of cyclists is hard to predict owing to potential large uncertainties. The DBN is used to infer the distribution of cyclists' intentions at intersections t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Other algorithms: In order to predict future trajectories, Dynamic Bayesian Networks (DBN) and other models have also begun to be used in some research. Hongbo GAO et al [31] used a fusion algorithm including DBN and LSTM to infer the intention distribution of cyclists at unsignaled intersections. Sinda Rebello et al [37] adopted DBN and HMM to estimate the reliability of the prediction function, but this method can only be used in the case of having recorded system-specific process data or state data.…”
Section: Prediction Algorithmmentioning
confidence: 99%
“…Other algorithms: In order to predict future trajectories, Dynamic Bayesian Networks (DBN) and other models have also begun to be used in some research. Hongbo GAO et al [31] used a fusion algorithm including DBN and LSTM to infer the intention distribution of cyclists at unsignaled intersections. Sinda Rebello et al [37] adopted DBN and HMM to estimate the reliability of the prediction function, but this method can only be used in the case of having recorded system-specific process data or state data.…”
Section: Prediction Algorithmmentioning
confidence: 99%
“…The state of the next time step is estimated based on the system model. A vehicle kinematic model with on-board sensor inputs is used for time updates, as depicted in Equation (3).…”
Section: Motion Updatementioning
confidence: 99%
“…Knowing an ego-vehicle's position, which is referred to as vehicle localisation, is indispensable for autonomous driving applications [1,2,3] and adaptive driver assistance systems (ADAS). Accurate localisation can help a navigation system provide more precise routing instructions.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that too many decomposition levels consumed too much time and memory, and too little decomposition levels could not capture spatial details well. Such methods are mainly applied to infrared images and medical image processing [20–22]. Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that too many decomposition levels consumed too much time and memory, and too little decomposition levels could not capture spatial details well. Such methods are mainly applied to infrared images and medical image processing [20][21][22]. Li et al proposed a multi-scale de-fogging fusion method for a single image, in which dark channels, clarity and significant features were used as the weight map for fusion, and multi-scale fusion was carried out from top to bottom through the multi-level pyramid decomposition strategy [23].…”
Section: Introductionmentioning
confidence: 99%